Subsídios à análise de crédito imobiliário no Brasil : um estudo exploratório no Estado do Rio de Janeiro - Costilla, Hessia Itta Guillermo (2007)
The objective of this report is to analise the Mortgage Credit in Rio de Janeiro. The main idea is to draw a map of this segment and indicate the institutions that work and compete among them. To achieve this objective it was realized a survey in the main financial institutions that offer Mortgage Credit in Rio de Janeiro. This research allows to know all aspects that are related to the process of purchasing a property according with the three estipulated profiles. Additionally, it is analised the evolution of the Mortgage credit in other countries, like Chile and United States, looking to learn with their experience and apply in Brazil.